Students’ Anxiety in Speaking English of The 10th Grade at SMA Negeri 16 Samarinda - Chyntia Tri Rahayu; Rahmat Soe'oed; Ventje Kalukar (English Department, Faculty of Teacher Training and Education, Mulawarman University, 2019)
Anxiety in speaking English is one of the affective factors that can influence language learning negatively. This study focused on exploring students’ anxiety of the 10th grade students at SMA Negeri 16 Samarinda, for investigating the speaking anxiety of the types, causes, and students’ strategies to overcome their anxiety in speaking English. This study utilized a case study, qualitative research design. The research subjects of this study were four students who categorized as high and moderate anxiety. The data were obtained from classroom observation and interviews. The data were transcribed and triangulated by using data triangulation. The result of the study revealed that one male student was categorized as high speaking anxiety experienced with trait anxiety. While the other male students was categorized as moderate speaking anxiety experienced with state anxiety. The two female students also experienced with state anxiety. The cause of these anxiety that experienced by student who has a type of trait anxiety was because of not accustomed to speaking or interacting with other people in the form of oral communication both in English and Indonesian. While the causes of anxiety experienced by students who has a type of state anxiety was due to fear of negative reaction like being laughed at and feeling nervous and shyness because they are not confidence when speaking English in front of the class. The lack of knowledge and vocabulary mastery, and dislike of English lesson possessed also caused anxiety in speaking in English experienced by four participants. To overcome the causes of speaking anxiety, the students use preparation, avoided eye contact, expresive reactions, and positive thinking as their strategies.